“Esophageal Atresia and Tracheo-Esophageal Fistula – Diagnosis, Treatment and Prognosis” - Pandya, Kashyap; Pancholi, Mukesh; Pandya, Ananyaa; Patel, Jagrutkumar (Journal of Neonatal Surgery, 2025)
Background:Esophageal atresia (EA) with or without tracheo-esophageal fistula (TEF) represents one of the most critical congenital anomalies of the neonatal period, often associated with high morbidity and mortality. It results from defective foregut development leading to discontinuity of the esophagus and abnormal communication with the trachea. Despite remarkable advancements in neonatal surgery and critical care, the management of EA/TEF in developing countries continues to pose significant challenges due to delayed diagnosis, associated anomalies, and limited neonatal surgical infrastructure. Aim:To study the clinical presentation, diagnostic modalities, surgical management, postoperative outcomes, and prognostic determinants in patients with esophageal atresia and tracheo-esophageal fistula. Methods:This observational study was conducted in the Department of Surgery at S.S.G. Hospital, Vadodara, Gujarat, over a period of five years and eight months (January 2020 – August 2025). A total of 100 neonates and infants diagnosed with EA/TEF were included. Data regarding demographic profile, clinical features, diagnostic findings, type of anatomical defect, associated anomalies, surgical procedures, and outcomes were collected. Surgical management included primary repair in stable patients and staged procedures in those with long-gap atresia or poor general condition. Postoperative outcomes were assessed in terms of survival, complications, and six-month functional results. Statistical analysis was performed using SPSS version 26, with a p-value <0.05 considered significant. Results:Out of 100 patients, 62 were males and 38 females, with a mean birth weight of 1.85 ± 0.04 kg (range 950 g to 4.0 kg). The majority (78%) presented within 48 hours of life, and Type C EA with distal TEF was the most common variant (86%). Associated congenital anomalies were detected in 41% of cases, mainly cardiac (18%) and anorectal (10%). Primary repair was performed in 82% of patients, staged repair in 12%, and esophagostomy with gastrostomy in 6%. The overall survival rate was 63%, while mortality (37%) was mainly attributed to low birth weight (14%), sepsis (12%), anastomotic leak (7%), and congenital heart disease (4%).. Among survivors, anastomotic stricture (10%), recurrent fistula (3%), and gastroesophageal reflux (18%) were the major postoperative complications. At six-month follow-up, 71% had good functional outcomes with adequate oral feeding and growth. Conclusion:Esophageal atresia with tracheo-esophageal fistula remains a major neonatal surgical emergency. Early diagnosis, preoperative stabilization, and timely surgical intervention are critical for improving outcomes. Primary repair remains the preferred approach in stable neonates. Survival is influenced by factors such as birth weight, sepsis, and associated anomalies. Multidisciplinary neonatal care and long-term follow-up are essential for reducing complications and optimizing quality of life.